PENGARUH DPK, CAR, LDR TERHADAP ROA YANG TERDAFTAR DI BEI - Indrawati, 09.05.52.0070; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2013)
The objective of this research is to analyze the effect of variable Third Party Fund, Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR) on Financial Performance (ROA). The sample in this study were banking companies listed in Indonesian Stock Exchange from 2008 to 2011.The data collected was analyzed using multiple regression.The result of this study show that TPF and LDR have a positive and significant impact on financial performance. On the other hand CAR has no influence on financial performance (ROA).Keywords: ROA, TPF, CAR and LDR